Are Technology-Driven Mobile Phone Applications (Apps) the New Currency for Digital Stent Registries and Patient Communication: Prospective Outcomes Using Urostentz App. (8th January 2021) - Hameed, B. M. Zeeshan; Shah, Milap J.; Naik, Nithesh; Amaresh, Mohan; Hegde, Padmaraj; Beary, Rahil Hussein; Jayadeva, Suraj; Somani, Bhaskar K.
Abstract : Background . Forgotten ureteral stents (FUS) and stent-related symptoms (SRS) lead to increased postprocedural emergency department visits and add to the psychological and financial burden of the patients. Purpose . To review the usage and benefits of ureteral stent tracking and symptom monitoring through a single smartphone-based application (App) platform with 2-way clinician-patient communication. This study also compared the features with other smartphone apps used for stent tracking. Materials and Methods . 100 patients were included in this single-center prospective study conducted between September 2019 and December 2019. Patients who had metallic or long-term indwelling stents, noncomprehensible patients, and those not willing to share their data were excluded from the study. Results . Of 100 patients, 92 downloaded the Urostentz application, and 72 (78.2%) patients answered the pictorial symptom questionnaire. Symptom score analysis suggested that 62 patients (86.1%) had stent-related symptoms of which 3 required readmission and underwent early stent removal. The mean stent duration was 17.2 + 3.5 days (range: 11–23 days), with 69% of patients having their stent removed on the scheduled date and 25% of patients requesting a change of their appointment via the App. Conclusion . In this study, there was no case of FUS encountered. The "Urostentz" App is a freely available patient safety stent tracking application that provides a secure and simplified interface, which can significantly reduce the incidence of FUS and provide digital remote assistance in the management of stent-related symptoms.